GERMINATION ENHANCEMENT IN GREEN GRAM (Vigna radiata L.) BY PRIMING WITH OIL CAKE EXTRACTS (Applied Biological Research, 2023)
The present study was aimed to evaluate the efficacy of some oil cake  extracts as seed priming agent and nutrient source to improve the seed  quality attributes. Studies were conducted on green gram cv. ‘CO 8’ to  identify the suitable oil cake extracts and optimize the concentration of oil cake extracts for seed priming. The extracts of oil cakes viz., groundnut,  sesame, coconut, cotton and neem were evaluated using variable  concentrations i.e. 5, 10, 15 and 20%. The seeds primed with oil cake  extracts increased seed quality attributes viz., speed of germination,  germination percentage, root and shoot length, dry matter production and  vigour index as compared to the hydro- and non-primed seeds. The extract  of coconut oil cake (15%) was identified as the best suitable seed priming  agent for green gram.
Keywords: Germination; green gram; oil cake extracts; seed priming